Ecological Challenges and the Modern Economic Development - I. V. Boiko (Управленческое консультирование)
Climate change and the other environmental problems have been threatening the business and economic sustainability in all over the world and undermine the human existence in general. The article examines various global challenges, stemming from the anthropogenic impact on the nature and assesses their economic consequences. Despite the international community endeavours to react on the environmental change in a number of agreements and actions, their positive effect is still low. The article states the limitation of the fiscal methods, applied for the climate change actions and underlines the lack of the holistic approach needed for overcoming the various types of the anthropogenic pressure on the nature. The proposition is made for classification of the environmental problems in terms of their impact on national economies. The effect of the environmental problems is more severe for the countries having the lower level in economic development, which means that overcoming the ecological problems could be successful when the less developed and falling behind countries have been catching up the more advanced nations. The technological restructurization of the national economies is represented as the main road for coping with the ecological problems. Russia represent a special case in within ecological problems, mostly determined by the substantial raw resources dependence of its economy, which reveals the necessity of technological restructurization of the national economy based on the drastically substitution of raw resources by the science ware and green production.